The role of Bone Morphogenetic Protein-2 in craniofacial osteogenesis: A literature review - I Gusti Putu Hendra Sanjaya; Sri Maliawan (Intisari Sains Medis, 2022)
Bone Morphogenetic Protein (BMP) is a type of growth factor that belongs to the Transforming Growth Factor Beta (TGF-B) group. Bone Morphogenetic Protein-2 (BMP-2) is recognized as one of the first commercially available osteoblast inductors. When new bone is needed, mesenchymal stem cells can develop into osteoblasts, which then implant as osteocytes in the bone, providing additional structure and support. The principal agent that differentiates stem cells into osteoblasts is BMP-2. BMP-2 will be released into the bone matrix or serum in performing their job. BMP-2 activates the SMAD1/5/8 signal via mediating the physiological action of type I and II serine/threoninekine receptors. The active SMAD protein will form a complex with the SMAD4 protein, translocate DNA to the nucleus, and bind to particular genes like Dlx-2/5, Osx, and transcription. According to a recent study, BMP-2 boosts osteogenic growth. BMPs are effective in the treatment of craniofacial defects in current research. The subjects of this paper are the molecular mechanism of BMPs and their involvement in the clinical application of craniofacial deformity patients.